Mengukur Trust dan Purchase Decision Produk Skincare: Studi Kasus Aplikasi Review di Jakarta - Kinthan Arum Rengganis Setiyadjid; Usep Suhud; Daru Putri Kusumaningtyas (Indo Publishing, 2026)
This study aims to analyze the influence of online customer reviews, customer perceived value, and service quality on trust and purchase decisions among Lemon8 app users searching for information on The Originote skincare products in Jakarta. This study uses a quantitative method with primary data collected through an online questionnaire from 225 Lemon8 user respondents in Jakarta, selected using a purposive sampling technique. Data were analyzed using the Statistical Package for the Social Sciences (SPSS) and Structural Equation Modeling (SEM) AMOS with the Maximum Likelihood Estimation approach. The results show that online customer reviews have no significant effect on trust or purchase decisions. Customer perceived value has a significant effect on trust, but does not have a direct effect on purchase decisions, so its influence works indirectly through trust as a mediator. Service quality is also not proven to have a significant effect on trust or purchase decisions. Conversely, trust has a positive and significant effect on purchase decisions, making it the most dominant factor in driving purchase decisions. These findings indicate that on social media-based review platforms like Lemon8, consumer trust is built more through customer perceived value than solely from reviews or the platform's service quality, and this trust is the main key that drives skincare product purchasing decisions.